PEMBELAJARAN TEKNOLOGI FIREWALL PADA MIKROTIK UNTUK MENINGATKAN KEAMANAN JARINGAN PROXI JARINGAN NUSANTARA - zahra, Nurazizah; Fergina, Anggun (MAJU : Indonesian Journal of Community Empowerment, 2025)
This service activity presents the results of a practical study regarding network security optimization using Mikrotik at PT Proxi. This research is a practical lesson about firewall technology on Mikrotik to improve network protection. A Mikrotik component that allows network managers to manage data flows according to predetermined guidelines. With a deep understanding of firewalls, the aim is to block potentially harmful access, develop network policies, and strengthen overall security. the services required to use the software are NMAP, to recognize the software used, monitor through network scanning and port scanning, and explore the existing network security system.  Thus, it is hoped that this activity will not only increase student capacity, but also provide benefits to the community in gaining more knowledge, in an effective way to strengthen network security technology around them.